Post pandemic career planning strategy for generation Z based on cultural and religion values - Muslihati Muslihati; Riskiyana Prihatiningsih; Widya Multisari; Arifah Wulandari; Nur Mega Aris Saputra; Agusto Da Costa (KONSELOR, 2023)
This study investigates career planning strategies for Generation Z in the post-COVID-19 pandemic era, emphasizing career theories and cultural and religious values. Through content analysis, the research reviews 8 articles on career planning grounded in cultural and religious values, alongside 10 articles on career theories and work values. The findings indicate that the career planning process encompasses self-understanding, understanding of career opportunities, planning, and career decision-making, which should integrate values such as faith, hard work, honesty, cooperation, and resilience. These values are represented in cultural heritage, including proverbs, poems, games, models, songs, rhymes, and advice. These insights significantly contribute to the study and practice of career planning in both formal and non-formal education settings.